Promoting national identity through higher education and graduate employment: reality in the responses and implementation of government policy in China. Issue 6 (2nd November 2018) - Mok, Ka Ho
ABSTRACT: In the last decade, the Chinese government has called for deep collaboration between Hong Kong, Macau (the two special administrative regions of China) and cities in Southern part of the country to foster economic and social development across the region. More recently, the Chinese government initiated a strategic project to develop the Pan-Pearl River Delta region into a Greater Bay Area like successful bay economies in Tokyo and Florida. This article sets out against the wider policy context to critically examine the reality in the responses and implementation of government policy in China when serious attempts have been made to encourage students originally from Hong Kong and Macau to study in Chinese universities in the Mainland and look for career development upon their graduation. This article has found that the promotion of national identity through higher education and graduate employment has not been successful because of failure of policy coordination, policy interpretations and implementation.